Incidence of and risk factors for surgical site infections in women undergoing hysterectomy for endometrial carcinoma. (22nd January 2016) - Tuomi, Taru; Pasanen, Annukka; Leminen, Arto; Bützow, Ralf; Loukovaara, Mikko
Abstract: Introduction: The purpose of this study was to determine the incidence of, and risk factors for, surgical site infections in a contemporary cohort of women with endometrial carcinoma. Material and methods: We retrospectively studied 1164 women treated for endometrial carcinoma by hysterectomy at a single institution in 2007–2013. In all, 912 women (78.4%) had minimally invasive hysterectomy. Data on surgical site infections were collected from medical records. Univariate and multivariate analyses were used to identify risk factors for incisional and organ/space infections. Results: Ninety‐four women (8.1%) were diagnosed with a surgical site infection. Twenty women (1.7%) had an incisional infection and 74 (6.4%) had an organ/space infection. The associations of 17 clinico‐pathologic and surgical variables were tested by univariate analyses. Those variables that were identified as potential risk factors in univariate analyses ( p < 0.15) were used in logistic regression models with incisional and organ/space infections as dependent variables. Obesity (body mass index ≥ 30 kg/m 2 ), diabetes, and long operative time (>80th centile) were independently associated with a higher risk of incisional infection, whereas minimally invasive surgery was associated with a smaller risk. Smoking, conversion to laparotomy, and lymphadenectomy were associated with a higher risk of organ/space infection. Conclusions: Organ/space infections comprised the majority of surgical site infections. Risk factors for incisional and organ/space infections differed. Minimally invasive hysterectomy was associated with a smaller risk of incisional infections but not of organ/space infections.